Advances in detection and analysis of modern evasive malware - Barr-Smith, F (2023)
Malware authors use a variety of techniques to avoid the sophisticated detection algorithms used by Antivirus (AV) and similar technologies. This is an area that has been subject to some open-source research in the form of academic research papers. Much of the closed-source research on this topic is contained within private organisations. This thesis is composed of the systematic study and analysis of these evasion techniques.